A virtual reality-based self-guided training on identification of negative automatic thoughts in healthy adults: a mixed-methods feasibility study - Yang, Bixi; Liao, Chenxi; Yang, Yuqing; Shi, Binbin; Zhang, Caidi; Li, Chunbo (Frontiers in Psychiatry, 2024)
BackgroundCognitive restructuring (CR) is an evidence-based psychological technique for depression. However, face-to-face CR is not easily accessible. Digital CR interventions often overlook the difficulties individuals experiencing depression encounter in identifying their negative automatic thoughts (NAT), leading to suboptimal outcomes. Virtual Reality (VR) has potential advantages in assisting the identification of NAT in CR intervention.ObjectiveThe aim of this preliminary feasibility study is to assess the efficacy, acceptability and safety of a VR-based self-guided training on the identification of negative automatic thoughts (VR-STINAT) for depression, as well as to evaluate the user experience.MethodsIn a mixed methods study, 20 healthy participants underwent VR-STINAT and completed a semi-structured interview, followed by post-training homework. The VR-STINAT includes three modules: psychological education, NAT identification training in VR scenarios, and practice in personally experienced scenarios. Effectiveness was measured via Thought Record Skills Assessment (TRSA) of homework and Cognitive Therapy Awareness Scale (CTAS). Acceptability was measured using an adapted Technology Acceptance Model and duration of training. Safety was measured via Simulator Sickness Questionnaire and self-reported negative emotions. Qualitative material was analyzed using thematic analysis.ResultsThe VR-STINAT was acceptable, with an average rating of 80.68%. The accuracy of NAT identification in TRSA reached 84.55%, and CTAS correctness reached 76.67%. The majority of participants experienced minimal or no side effects, although a few (10%, 2/20) reported relatively severe fatigue and craniofacial pain. Thematic analysis reviewed four themes: effectiveness, acceptability, advantages of VR, difficulties in use and suggestions for improvement. Most participants indicated that they’ve learned how to identify their NAT through VR-STINAT (85%, 17/20), which was engaging (90%, 18/20) and easy to use (60%, 12/20).ConclusionThis study provides preliminary evidence that self-guided training for the identification of negative automatic thoughts related to depression using VR is feasible. Future studies are needed to compare the efficacy of VR with other intervention modalities in people with depression.